Raman scattering in La1−xSrxFeO3−δ thin films: annealing-induced reduction and phase transformation. (27th March 2015) - Islam, Mohammad A; Xie, Yujun; Scafetta, Mark D; May, Steven J; Spanier, Jonathan E
Abstract: Raman scattering in thin film La0.2 Sr0.8 FeO3− δ on MgO(0 0 1) collected at 300 K after different stages of annealing at selected temperatures T (300 K < T < 543 K, to 10 h) and analysis reveal changes in spectral characteristics due to a loss of oxygen, onset of oxygen vacancy-induced disorder, and activation of Raman-inactive modes that are attributed to symmetry lowering. The interpretation is further supported by carrier transport measurements under identical conditions showing orders of magnitude increase in the resistivity induced by oxygen loss. After prolonged annealing in air, evolution of the spectrum signals the appearance of a possible topotactic transformation of the crystal structure from that of the rhombohedral AB O3 perovskites to that of Brownmillerite-like structure consisting of octahedrally and tetrahedrally coordinated Fe atoms.